2022
DOI: 10.1007/s00213-021-06039-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting for a quinoline containing selenium for comorbidities depression and memory impairment induced by restriction stress in mice

Abstract: Rationale Depression is often associated with memory impairment, a clinical feature of Alzheimer’s disease (AD), but no effective treatment is available. 7-Chloro-4-(phenylselanyl) quinoline (4-PSQ) has been studied in experimental models of diseases that affect the central nervous system. Objectives The pharmacological activity of 4-PSQ in depressive-like behavior associated with memory impairment induced by acute restraint stress (ARS) in male Swiss mice was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Another compound, 7-chloro-4-(phenylsenyl) quinoline (4-PSQ), was also recently shown by de Oliveira and colleagues to be effective in attenuating depressive-like phenotypes in mice following acute restraint stress (ARS) [ 229 ]. Among other mechanisms, the researchers reported that direct attenuation of the HPA axis activation may be involved in this finding, as 4-PSQ treatment prior to ARS maintained circulating corticosterone (CORT), the main active GC in mice, at levels similar to those of the unstressed controls [ 229 ]. This suggested that prophylactic administration of 4-PSQ might have the capacity to prevent hyperactivation of the HPA axis, keeping CORT levels near baseline.…”
Section: Signals From Brain To Bodymentioning
confidence: 99%
“…Another compound, 7-chloro-4-(phenylsenyl) quinoline (4-PSQ), was also recently shown by de Oliveira and colleagues to be effective in attenuating depressive-like phenotypes in mice following acute restraint stress (ARS) [ 229 ]. Among other mechanisms, the researchers reported that direct attenuation of the HPA axis activation may be involved in this finding, as 4-PSQ treatment prior to ARS maintained circulating corticosterone (CORT), the main active GC in mice, at levels similar to those of the unstressed controls [ 229 ]. This suggested that prophylactic administration of 4-PSQ might have the capacity to prevent hyperactivation of the HPA axis, keeping CORT levels near baseline.…”
Section: Signals From Brain To Bodymentioning
confidence: 99%
“…Additionally, the synthesis of new molecules containing the selenium atom has attracted great interest in organic synthesis and medicinal chemistry due to the broad and interesting pharmacological properties attributed to these compounds. 10 Reports demonstrate that organoselenium compounds show antidepressant, 11 anticancer, 12 anti-Alzheimer's disease, 13 and antiviral activities. 14 Furthermore, recent studies have shown that the incorporation of selenium into organic molecules, especially in the heterocyclic core, can considerably increase the pharmacological activities of these compounds.…”
Section: Introductionmentioning
confidence: 99%